Effects of different recovery methods on postboxing sparring fatigue substances and stress hormones - Tianlong, D.; Sim, Y.-J. (Journal of Exercise Rehabilitation, 2019)
This study aimed to investigate the effects of static rest, massage, aromatherapy, and acupoint acupressure on the levels of fatigue substances and stress hormones produced after a session of boxing sparring. The study was conducted on female adolescent boxers (n=12) who underwent four recovery methods with a 7-day rest period between each session. The order of these methods was decided randomly. Prior to each method, the participants performed five rounds of 4-min boxing sparring, and the maximal intensity was set as 70%-80% of the maximal heart rate. The effects of the four recovery methods on the blood levels of fatigue substances and stress hormones after boxing sparring were investigated. Static rest, massage, aromatherapy, and acupoint acupressure significantly decreased the lactic acid levels. The creatine phosphokinase levels decreased in the aromatherapy and acupoint acupressure groups, while the lactate dehydrogenase levels significantly decreased in the massage, aromatherapy, and acupoint acupressure groups. Further, the levels of stress hormones, cortisol, and epinephrine, showed no significant changes after massage and acupoint acupressure. However, a significant decrease in the cortisol level was observed in the aromatherapy group and an increasing trend was observed in the cortisol level in the static rest group. The adrenocorticotropic hormone level significantly decreased in the aromatherapy group and showed a decreasing trend after the participants received massage or acupoint acupressure. High-intensity exercise results in not only physical, but also psychological fatigue. Massage and aromatherapy can improve the physical and psychological stabilities and performances of athletes.